Young Adults and Active Citizenship : Towards Social Inclusion Through Adult Education - Kersh, Natasha; Toiviainen, Hanna; Pitkänen, Pirkko; Zarifis, George K. (Lifelong Learning Book, 2021)
This open access book sheds light on a range of complex interdependencies between adult education, young adults in vulnerable situations and active citizenship. Adult education has been increasingly recognized as a means to engage and re-engage young adults and facilitate their life chances and social inclusion thus contributing to an active citizenship within their societal contexts. This collection of chapters dealing with issues of social inclusion of young people represents the first book to explicitly approach the complex interdependencies between adult education, young adults in vulnerable situations and active citizenship from the European perspective. Social exclusion, disengagement and disaffection of young adults have been among the most significant concerns faced by EU member states over the last decade. It has been increasingly recognised by a range of stakeholders that there is a growing number of young people suffering from the various effects of the unstable social, economic and political situations affecting Europe and its neighbouring countries. Young adults who experience different degrees of vulnerability are especially at risk of being excluded and marginalised. Engaging young adults through adult education has been strongly related to addressing the specific needs and requirements that would facilitate their participation in social, economic and civic/political life in their country contexts. Fostering the active citizenship of young people, both directly and indirectly, is an area where many AE programmes overlap, and this has become a core approach to integration. This book considers social, economic and political dimensions of active citizenship, encompassing the development of social competences and social capital, civic and political participation and the skills related to the economy and labour market. The cross-national consideration of the notions of vulnerability, inclusion and active citizenship underpins the complexity of translating these concepts into the national contexts of adult education programmes.
Keywords: Educació d'adults; Ciutadania; Lifelong Learning/Adult Education; Sociology of Citizenship; Sociology of Education; Social Structure, Social Inequality; Life Skills; Education; Biotechnology; Social Structure; Open Access; Adult Education in Europe; Active participatory citizenship; Lifelong learning for Vulnerable young adults; Comparative adult education; EduMAP project; Social inclusion; Horizon 2020 project; Adult Education as a Means to Active Participatory Citizenship; Development of social, political and economic skills; Active participatory citizenship (APC); Adult education, continuous learning; Sociology; Social research & statistics; Social & ethical issues; Study & learning skills: general